Aphasia's Implications for Linguistics Research Exploring the Interface Between Semantics and Pragmatics - Graci, Roberto (Cham : Springer International Publishing : Imprint: Springer, 2023)
This volume stresses the importance of a multidisciplinary perspective in deepening knowledge of the interface between semantics and pragmatics. It thoroughly investigates concepts belonging to Neo-Gricean and post-Gricean theories. Theoretical research in pragmatics has challenged the idea of a close relation between literal meaning and the explicitly conveyed proposition, claiming that situational context is responsible for an ongoing process of adjusting and revising what a speaker says. Similarly, recent discoveries from the clinical side have highlighted the importance of extra-linguistic sources and the cognitive context in the syntactic and semantic competence of people with language disorders. The productive comparison between reflections from theoretical pragmatics and the most recent developments in cognitive sciences provides an authentic way of addressing traditional philosophical issues, moving them to a new fertile ground. The research herein is gathered across disciplines to provide theoretical and clinical contributions and collaborations, making this book broadly appropriate to students, researchers and professionals in the fields.
Introduction -- Chapter 1. The Intersection of Philosophy and Linguistics in Understanding Language Pathologies -- Chapter 2. Understanding the Significance of Situational Context and Common Ground in Communication -- Chapter 3. The Semantics/Pragmatics Interface -- Chapter 4. The Cognitive Substrates of Pragmatics -- Chapter 5. Aphasia, Sub-Sentential Speeches and Pragmatic Enrichment -- Concluding Remarks and Future Directions for the Semantics/Pragmatics Debate.
Keywords: Linguistics; Clinical psychology; Language and languages -- Philosophy; Cognitive science; Theoretical Linguistics / Grammar; Clinical Psychology; Philosophy of Language; Cognitive Science